A challenging case of jaundice and febrile uncommon rash in an immunocompetent male patient - Gheorghiță, Valeriu; Radu, Adelina Maria; Sălăvăstru, Carmen Maria; Socoliuc, Claudiu; Ștefan, Ion (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Gheorghiță V, Radu AM, Sălăvăstru CM, Socoliuc C, Ștefan I. A challenging case of jaundice and febrile uncommon rash in an immunocompetent male patient. Turk J Gastroenterol 2019; 30(5): 485-8.